2020
DOI: 10.1186/s12955-020-01378-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcultural adaptation and validation of a Korean version of the Oxford Ankle Foot Questionnaire for children

Abstract: Background The purpose of this study was to translate and transculturally adapt the original English version of the Oxford Ankle Foot Questionnaire (OAFQ) into a Korean version, and to evaluate its psychometric properties. Methods A Korean OAFQ for children was developed according to established guidelines. To test validity, 169 consecutive patients with foot and ankle problems and their caregivers each completed the OAFQ. The children also completed a Korean version of the KIDSCREEN-52 health related quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Structural validity : The structural validity was evaluated for six PROMs. 22 , 29 , 33 , 44 , 51 , 52 Three studies reported on the structural validity of a cultural adaption of the original PROMs. 29 , 44 , 52 All studies 22 , 29 , 33 , 44 , 51 , 52 failed to report on the important aspects of the item-related theory or Rasch analyses and did not describe the model fit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural validity : The structural validity was evaluated for six PROMs. 22 , 29 , 33 , 44 , 51 , 52 Three studies reported on the structural validity of a cultural adaption of the original PROMs. 29 , 44 , 52 All studies 22 , 29 , 33 , 44 , 51 , 52 failed to report on the important aspects of the item-related theory or Rasch analyses and did not describe the model fit.…”
Section: Resultsmentioning
confidence: 99%
“… 22 , 29 , 33 , 44 , 51 , 52 Three studies reported on the structural validity of a cultural adaption of the original PROMs. 29 , 44 , 52 All studies 22 , 29 , 33 , 44 , 51 , 52 failed to report on the important aspects of the item-related theory or Rasch analyses and did not describe the model fit. The results of the PROMs did not meet the COSMIN criteria for good measurement properties.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of foot and ankle conditions was measured using the Oxford Ankle Foot Questionnaire (OxAFQ) [ 17 ]. OxAFQ has been developed and validated to measure the impact of foot and ankle conditions on aspects of life that are considered important for children [ 17 , 18 ]. The questionnaire consists of 15 items rated on a 5-point Likert scale (0, always; 1, very often; 2, sometimes; 3, rarely; and 4, never), the first 14 of which are used to calculate subscale scores, and comprises three subscales (physical, 6 items; school and play, 4 items; emotional, 4 items; and footwear as an additional item).…”
Section: Methodsmentioning
confidence: 99%
“…About Internal consistency most of the versions analyzed (39,41,44,45) reported an excellent value except for MOXFQ (43) and OAFQ (42) where there was a high range between the various domains however all the Italian questionnaires analysed were on average in line with the versions available in other languages, however some exceptions are observed such as for example AOFAS Persian (98) version shows a substantially lower value (α=0.696) than the Italian version (39) ( α=0.92-0.95) nonetheless was considered acceptable, or FFI Brazilian-Portuguese version (103) have a lower value (α=0.80-0.86) compared to Italian version (αC = 0.96 or nally the higher values reported by the Chinese (α=0.991-0.976) (104) and French (α=0.79-0.94) (105) MOXFQ version. Four of the Italian questionnaires selected for ankle and the foot (39,41,43,45) assessed Construct validity using correlation with Sf-36 and this last comparison tool is also found in questionnaires in other languages such as for example in AOFAS in all analyzed versions (106-110) while contrary MOXFQ-Chinese version (104) and FFI Spanish and Chinese versions (52,111) used in common SF-12V2 and EuroQoL5D, or for example OAFQ versions different from the Italian one assessed mainly with the Kidscreen (112,113).…”
Section: Psychometric Variables Of Questionnaires For the Assessment ...mentioning
confidence: 99%